The Importance and Effectiveness of Inclusive Education at School - Nasirova Muxtabar Abduraximovna (Next Scientists International Journal JSSHRF, 2026)
This article comprehensively analyzes the importance and effectiveness of inclusive education in schools and its impact on students’ personal, academic, and social development. During the research process, based on modern pedagogical literature and scientific research results, the methodological principles of inclusive education, the process of teachers’ professional development, as well as the impact of the use of digital and innovative technologies on pedagogical effectiveness were studied. The results showed that inclusive education not only serves to improve academic performance, but also helps develop students’ social adaptation ability, teamwork skills, empathy, and personal responsibility. The research also emphasizes the importance of special training of teachers and the effective use of inclusive methodologies, as well as the role of technological tools in individualizing and optimizing the educational process. The results of the paper serve as a basis for forming practical recommendations on the widespread implementation of inclusive education in schools, improving the quality of education, and ensuring equal opportunities.